A Microfluidic Device for Long‐Term Maintenance of Organotypic Liver Cultures. Issue 2 (3rd October 2022) - de Hoyos‐Vega, José M.; Hong, Hye Jin; Loutherback, Kevin; Stybayeva, Gulnaz; Revzin, Alexander
Abstract: Liver cultures may be used for disease modeling, testing therapies, and predicting drug‐induced injury. The complexity of the liver cultures has evolved from hepatocyte monocultures to co‐cultures with non‐parenchymal cells and finally to precision‐cut liver slices. The latter culture format retains liver's native biomolecular and cellular complexity and therefore holds considerable promise for in vitro testing. However, liver slices remain functional for ≈72 h in vitro and display limited utility for some disease modeling and therapy testing applications that require longer culture times. This paper describes a microfluidic device for longer‐term maintenance of functional organotypic liver cultures. This microfluidic culture system is designed to enable direct injection of liver tissue into a culture chamber through a valve‐enabled side port. Liver tissue is embedded in collagen and remained functional for up to 31 days, highlighted by continued production of albumin and urea. These organotypic cultures also express several enzymes involved in xenobiotic metabolism. Conversely, matched liver tissue embedded in collagen in a 96‐well plate loses its phenotype and function within 3–5 days. The microfluidic organotypic liver cultures described here represent a significant advance in liver cultivation and may be used for future modeling of liver diseases or for individualized liver‐directed therapies. Abstract : A microfluidic device is developed for cultivating intact liver tissue. Maintenance of hepatic function (e.g., albumin and urea) is demonstrated for 30 days in this microfluidic device. Additional analyses demonstrate that microfluidic liver cultures retain native cytoarchitecture, produced bile and expressed phase 1 and phase 2 enzymes.